1998
DOI: 10.1034/j.1600-0412.1998.770204.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of human placental lactogen, pregnancy‐associated plasma protein A and endometrial secretory protein PP14 in first trimester of diabetic pregnancy

Abstract: In first trimester of diabetic pregnancy there appears to be both a more general depression of trophoblast function, and also a specific depression of the hPL release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 11 publications
3
24
0
1
Order By: Relevance
“…19 Another study failed to detect this correlation in pregnant women with insulin-dependent DM. 17 Similarly, we identified no correlation between PAPP-A and HbA1c levels in women with GDM. These observations suggest that PAPP-A may not be useful for assessing or predicting glycaemic control in women with GDM due to the relatively short duration of women's exposure to GDM that is confined to the latter part of pregnancy.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…19 Another study failed to detect this correlation in pregnant women with insulin-dependent DM. 17 Similarly, we identified no correlation between PAPP-A and HbA1c levels in women with GDM. These observations suggest that PAPP-A may not be useful for assessing or predicting glycaemic control in women with GDM due to the relatively short duration of women's exposure to GDM that is confined to the latter part of pregnancy.…”
Section: Discussionmentioning
confidence: 66%
“…[12][13][14] Several studies have shown that women with pre-existing diabetes mellitus (DM) have significantly lower PAPP-A levels than those without DM. 11,[15][16][17][18] Besides, PAPP-A levels in non-pregnant individuals with type 2 DM correlate inversely with glycosylated haemoglobin (HbA1c) levels. 19 These observations suggest that PAPP-A levels may reflect the degree of glycaemic control.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest IGF in 3 rd trimester was associated with macrosomia which others cannot substantiate [31]. With focus on timing of sampling, subsequent studies find high levels of IGF in 1 st trimester associated with early growth delay measured by ultrasound [32,33]. Inclusion of patients with various degrees of nephropathy precludes firm conclusion in pregnancy.…”
Section: Temporal Review Of Studies On Fetal Growth and The Igf Systemmentioning
confidence: 99%
“…A possible reduction in early fetal growth potential may be seen with low levels of IGFBP-3 proteolysis early in singleton diabetic pregnancy [32]. One study shows high levels of IGFBP-3 measured by RIA where one third of fetuses exhibit 'early growth delay' judged by ultrasound in first trimester [32]. In contrast levels of IGFBP-3 and IGFBP-3 protease activity increases in maternal serum in very early in multiple pregnancies [29].…”
Section: Maternal Compartmentmentioning
confidence: 99%
See 1 more Smart Citation